2020
DOI: 10.1108/pr-04-2020-0214
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of person-supervisor fit in relationship quality and well-being of university academicians

Abstract: PurposeThe purpose of this paper is to examine how the quality of a subordinate's relationship with his or her direct supervisor influences the subordinate's psychological well-being and to examine the moderating role of person-supervisor (P-S) fit between these two variables.Design/methodology/approachThe sample for this study consists of 418 academic employees of two federal universities. Relationship quality, P-S fit, psychological well-being and demographics were self-reported by the participants using exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…This indicates that the impact of ethical leadership on employees may depend on several individual factors. This conclusion addresses Enwereuzor et al's [72] call for more researchers to examine P-S fit as a moderator. Subordinates who have similar values and work styles as their superiors will have more affective well-being.…”
Section: Theoretical Implicationssupporting
confidence: 56%
See 1 more Smart Citation
“…This indicates that the impact of ethical leadership on employees may depend on several individual factors. This conclusion addresses Enwereuzor et al's [72] call for more researchers to examine P-S fit as a moderator. Subordinates who have similar values and work styles as their superiors will have more affective well-being.…”
Section: Theoretical Implicationssupporting
confidence: 56%
“…Recent research also found a positive relation between P-S fitness and job satisfaction [69][70][71]. Additionally, Enwereuzor et al [72] found that a good P-S fit is related to higher mental health levels because the subordinates' interests are in good alignment with their superiors' interests, and they get along well. Therefore, there are no confrontations or conflicts between supervisors and subordinates due to different interests.…”
Section: Moderation Of Moral Identitymentioning
confidence: 97%
“…On the moderating effects of the P-S fit, several investigations have been conducted. The P-S fit highlights the mutual appreciation in subordinate-supervisor relationships that promotes understanding of and support for each other (Enwereuzor et al, 2021;Kim and Kim, 2013). According to our study, the P-S fit is a crucial aspect in assessing leader humility's influence on the relational energy of workers.…”
Section: Person-supervisor Fit As the Moderatormentioning
confidence: 64%
“…It indicates employees' satisfaction with their work, tangible and intangible working environments, and the realization of value generated by the work. 9,39 Human thinking is accompanied by a variety of subjective feelings, including moods, emotions, cognitive feelings, and bodily experiences. The perception of occupational stigma at physical and social levels directly affects food-delivery workers' subjective feelings listed previously.…”
Section: Occupational Stigma and Workplace Well-being Of Gig Workersmentioning
confidence: 99%
“…Workplace well-being can be defined as employees' attitudes and feeling toward their working environment. It indicates employees' satisfaction with their work, tangible and intangible working environments, and the realization of value generated by the work 9,39 . Human thinking is accompanied by a variety of subjective feelings, including moods, emotions, cognitive feelings, and bodily experiences.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%